2014
DOI: 10.3892/or.2014.3108
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tumor size as a useful marker for the surgical staging of endometrial cancer

Abstract: Abstract. Accumulating evidence suggests that the estimation of tumor size may improve endometrial cancer treatment. We conducted an observational study aimed at elucidating the association between tumor size and other universally accepted prognostic factors in order to identify suitable preoperative parameters which can guide surgery in a subgroup of early corpus endometrial cancer. We found that when tumor size increased, both stage and grading were significantly increased. Tumor size was correlated with CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…EEC is typically associated with a lower aggressiveness and an improved long-term disease-free survival following adequate treatment compared with that of other ECs (24). Histology, depth of MI, tumor grade, presence of LVSI, positive peritoneal cytology, tumor size and LNS have been universally recognized as prognostic factors for determining long-term clinical course of the disease (25,26). Although certain studies have evaluated the association between AM and the clinical course of EEC, the mechanism by which AM interferes with tumoral progression remains unresolved (9,12,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…EEC is typically associated with a lower aggressiveness and an improved long-term disease-free survival following adequate treatment compared with that of other ECs (24). Histology, depth of MI, tumor grade, presence of LVSI, positive peritoneal cytology, tumor size and LNS have been universally recognized as prognostic factors for determining long-term clinical course of the disease (25,26). Although certain studies have evaluated the association between AM and the clinical course of EEC, the mechanism by which AM interferes with tumoral progression remains unresolved (9,12,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The median length of post-operative hospitalization was 3 days (2-5) in Group-0, 6 days (3-10) in Group-1 and 4 days (3)(4)(5)(6)(7)(8) in Group-2. The length of hospitalization for the three groups was significantly different between Group-0 vs Group-1 (p<0.001), between Group-0 vs Group-2 (p=0.006) and between Group-2 vs Group-1 (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Pelvic lymph nodes removal was performed according to grading (grade 3 or grade 2 with estimated myometrium invasion more than 50 %) and preoperative imaging features (bulky lymph nodes, myometrium invasion more than 50 %, estimated tumor size larger than 3 cm) [8].…”
Section: Methodsmentioning
confidence: 99%
“…If RAL anticancer activity in endometrial cells can be confirmed, a further topic of study could be the evaluation of its preoperative use in reducing endometrial tumor size and improving the overall estimated oncological risk (Berretta et al, 2014;Gizzo et al, 2014c).…”
Section: Discussionmentioning
confidence: 98%